Knickerbocker : The Myth behind New York - Bradley, Elizabeth L. (Book collections on Project MUSE., 2009)
Bradley's stunning volume offers a surprising and delightful glimpse behind the scenes of New York history, and invites readers into the world of Diedrich Knickerbocker, the antihero who surprised everyone by becoming the standard-bearer for the city's exceptional sense of self, or what we now call a New York "attitude." A 2010 AAUP Best of the Best title "A briskly engaging book." --Christopher Benfey, New York Review of Books "This is cultural history at its best." --Journal of American Culture "Elizabeth L. Bradley sorts, catalogues and deciphers the shifting Knickerbocker currents in a metropolis constantly reinventing itself. She does the sturdy Dutchman proud in a scholarly and polished rendition." --Star-Ledger "Bradley creates an engaging account of the city through the fictional Knickerbocker, who was a steady presence 'over two centuries of wrenching urban transformation, from the post-colonial to the postmodern.' Bradley is a perceptive and lively writer and does a superb job of tracing the many strands of the Knickerbocker myth. She provided the historical context necessary to illustrate the ways the Knickerbocker brand was invoked and provides deft analysis of the cultural meanings it accrued." --Bookforum.